PUBLIC TRANSPORTATION: WISH FULFILLMENT AND REALITY IN THE SAN FRANCISCO BAY AREA - Merewitz, Leonard (American Economic Review, 1972)
THIS REPORT DISCUSSES SPECIFICATIONS, COSTS, TIME TO COMPLETION AND PATRONAGE OF THE BAY AREA RAPID TRANSIT (BART) SYSTEM. ALSO DISCUSSED ARE COORDINATION AMONG TRANSIT PROPERTIES (FEEDER SERVICES), FINANCE, AND ACCEPTANCE AMONG USERS. DEMAND FOR BART RIDES WILL BE A FUNCTION OF THE PRICE OF BART AND THE PRICE OF OPERATING AN AUTOMOBILE. THERE IS A GOOD CASE FOR INCREASING THE PRICE OF AUTO USE, SINCE AUTOS DO NOT PAY THEIR MONETIZED COSTS. THE ECONOMIC LOGIC IS THAT MASS TRANSIT MAKES ROADS LESS CONGESTED; THEREFORE ROAD USERS OUGHT TO SHARE IN THE COSTS OF RAPID TRANSIT. THE MAJOR BENEFITS OF BART ARE YET TO BE SEEN. LAND USE AND URBAN DEVELOPMENT GOALS WERE ALSO OF PRIMARY IMPORTANCE TO THE PLANNERS. AN INTERDISCIPLINARY GROUP, INCLUDING TRANSPORTATION ENGINEERS, ECONOMISTS, CITY PLANNERS, AND PSYCHOLOGISTS, HAS ORGANIZED TO MONITOR THE IMPACT OF BART ON THE SAN FRANCISCO BAY AREA FOR AT LEAST THE NEXT TEN YEARS. /AUTHOR/